An Analysis on the Legal Framework for Combating Child Labour in India: Addressing the Challenges of Child Labour in India: A Holistic Approach (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A few laws have been passed in India to ensure and advance the rights of children. In any case, child work measurements and different insights point to the fact that these laws have not been extremely powerful. Request and supply powers exist to sustain child work and to keep the economy at a low balance trap. Unless the fundamental causes of child work are tended to, the rights of the child will never be secured. The paper requires an all encompassing way to deal with address the issue of child work and endeavors to give a model of child support arrange that is obvious and available to a child in trouble. The three basic parts of such an approach is (I) to offer help to the bothered families to evacuate their reliance on child work, (ii) an updating of the education system to influence it to react to the requirements of the economy and (iii) a successful child support system that is coordinated with the neighborhood governance structure. These three parts are not to supplant but rather to supplement the current measures.